Zasady współdziałania partnerów w procesach tworzenia wartości dla klienta - Gwarda-Gruszczyńska, Edyta (Principles of Partnership in Process of Customer Value Creation, 2005)
Today many markets are organized as networks of companies. The companies to compete successfully try to gain mutual target witch is customer value. If they succeed they reach the effects like: additional synergy effects and competitive advantage. To do it, however, companies must create and use in practice some basic rules. In this article the author concentrates on some chosen rules that should drive partners' relationships within the network, including 3C rules (connectivity, community, collaboration).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 66-73